Pengaruh Profitabilitas, Ukuran Perusahaan, Tanggung Jawab Sosial Dan Struktur Modal Terhadap Nilai Perusahaan - Unenor, Ignacia Griseldis Shan; Falah, Syaikul; Prasetyo, Bucek Jalu (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
This study aims to analyze the influence of profitability, company size, corporate social responsibility, and capital structure, both partially and simultaneously, on the value of the company. This study uses a quantitative approach with a causality study method to find the influence between variables. The data used is secondary data in the form of financial statements of food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The research sample was selected using the purposive sampling technique, resulting in 20 sample companies or a total of 60 observations for three consecutive years. The analysis tool used in this study is the Eviews 12 software. The results of the partial test research show that profitability (Return On Equity) has a positive and significant effect on the company's value, in line with the Signal Theory that high profits give a positive signal to investors. Company size (Total Assets) has a negative and significant effect on the company's value. Corporate social responsibility (CSR) and capital structure (Debt to Equity Ratio) do not have a significant partial effect on the company's value. However, simultaneously, profitability, company size, social responsibility, and capital structure have a significant effect on the value of the company. A determination coefficient (R²) of 0.482591 indicates that 48% of the variation in the company's value can be explained by these variables, while 52% is explained by other factors outside the model.